New record of the genus Zombrus Marshall, 1897 (Hymenoptera: Braconidae: Doryctinae), with description of three new species from Vietnam - Long, Khuat Dang; van Achterberg, Cornelis; Hoa, Dang Thi (Zootaxa, 2018)
The genus Zombrus Marshall, 1897, is newly recorded for Vietnam with four species. Three new species (Z. bicoloricorpus Long, sp. n., Z. flavicorpus Long & van Achterberg, sp. n., and Z. tricoloricorpus Long, sp. n.) are described and illustrated, and one species (Z. pallidiventris Cameron, 1910) is reported for the first time from Vietnam and outside Indonesia. The key to Oriental and Palaearctic species of Zombrus and a checklist with distributions of the nine species from Oriental and Palaearctic regions are provided.